Transcription of Bacteriophage PM2 Involves Phage-Encoded Regulators of Heterologous Origin - Männistö, Riina H. (American Society for Microbiology, 2003)
Bacteriophage PM2 is the only described member of the Corticoviridae family. It is an icosahedral dsDNA virus with a membrane residing underneath the protein coat. PM2 infects some gram-negative Pseudoalteromonas spp. In the present study, we mapped the viral promoters and showed that the PM2 genome consists of three operons. Four new virus genes were assigned based on their function in transcription. Proteins P15 and P16 are shown to repress early transcription, and proteins P13 and P14 are shown to activate late transcription events. The early regulatory region, containing genes for proteins P15 and P16, as well as the newly identified early promoter region in PM2, has significant sequence similarity with the Pseudoalteromonas pAS28 plasmid. P14, the transcription activator for the structural genes, has a zinc finger motif homologous to archaeal and eukaryotic TFIIS-type regulatory factors.